2014
DOI: 10.1590/s0100-204x2014000800007
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de carbono em Latossolo adubado com dejeto líquido de suínos e cultivado em plantio direto

Abstract: Resumo -O objetivo deste trabalho foi estimar taxas de acúmulo de C orgânico em Latossolo Vermelho adubado com adubo solúvel e dejeto líquido de suíno e cultivado em plantio direto. O experimento foi conduzido em Campos Novos, SC, e os seguintes tratamentos foram aplicados anualmente: sem adubação; adubo solúvel; 25 m 3 ha -1 de dejeto líquido + adubo solúvel; e doses de 25, 50, 100 e 200 m 3 ha -1 de dejeto líquido. Foram determinados: os estoques de C orgânico (CO) na camada de 0-20 cm do solo; a adição de C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
2
25
0
3
Order By: Relevance
“…The result of treatment PS + SF was noteworthy, for being similar to PS100 and PS200 and higher Mafra et al (2014) in another study in the same experimental area. These authors reported that the combined treatment PS + SF resulted in a biomass yield similar to the treatments with highest PS rates and this yield was positively correlated with the TOC fixation rate in the soil (Mafra et al, 2014).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The result of treatment PS + SF was noteworthy, for being similar to PS100 and PS200 and higher Mafra et al (2014) in another study in the same experimental area. These authors reported that the combined treatment PS + SF resulted in a biomass yield similar to the treatments with highest PS rates and this yield was positively correlated with the TOC fixation rate in the soil (Mafra et al, 2014).…”
Section: Resultssupporting
confidence: 71%
“…These authors reported that the combined treatment PS + SF resulted in a biomass yield similar to the treatments with highest PS rates and this yield was positively correlated with the TOC fixation rate in the soil (Mafra et al, 2014).…”
Section: Resultsmentioning
confidence: 89%
“…Specific recommendations include the development of critical P limits (Gatiboni et al, 2015) to obtain the expected benefits from the chemical, physical, and biological properties of the soil and subsequent crop yield (Mafra et al, 2014;Grave et al, 2015). The concept has been adopted that organic fertilizers help promote system sustainability and should not be regarded as a potential source of environmental pollutants (Lourenzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Under this scenario, environmental agencies have shown great concern, since when the soil bearing capacity is exhausted, this waste can cause a large amount of environmental damage (SEIDEL et al, 2010). In this regard, studies investigating water reuse in the environment have gained importance, and are usually related to physical-chemical changes in the soil (CAMPOS et al, 2012;LUCAS et al, 2013;MENEGHETTI et al, 2013;KESSLER et al, 2013;KESSLER et al, 2014;MAFRA et al, 2014), contamination of surface and groundwater (MAGGI et al,. 2011;BOLZANI, OLIVEIRA and LAUTENSCHLAGER 2012;MAGGI et al, 2013;CAPOANE et al, 2015), and the contribution to crop productivity (MENEGHETTI et al, 2012;CAMPOS et al, 2013).…”
Section: Introductionmentioning
confidence: 99%